Malaria outbreak in relation to a cluster of imported cases in a border area, Peru - Solis-Castro, María Edith (2022)
Background: Malaria is transmitted by the bite of mosquitoes of the Anopheles genus. The Tumbes region located on the northern border of Peru, despite the permanent presence of the vector, was free of malaria, presenting only sporadic imported cases. Material and Methods: A case series study of an outbreak of malaria caused by P. vivax associated with a conglomerate of imported cases was carried out in the context of massive Venezuelan migration to Peru. Results: The control activities implemented through the modified epidemiological fence methodology to control the reintroduction of the disease are described; transmission of the outbreak related to Venezuelan migrants in transit was detected.  Conclusions: the reintroduction of malaria in the Tumbes region was related to cases imported by Venezuelan migration. The modified epidemiological fences made it possible to improve the collection of cases in situ.